2016
DOI: 10.1099/jgv.0.000483
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific and individual differences in Nipah virus replication in porcine and human airway epithelial cells

Abstract: Highly pathogenic Nipah virus (NiV) causes symptomatic infections in pigs and humans. The severity of respiratory symptoms is much more pronounced in pigs than in humans, suggesting species-specific differences of NiV replication in porcine and human airways. Here, we present a comparative study on productive NiV replication in primary airway epithelial cell cultures of the two species. We reveal that NiV growth substantially differs in primary cells between pigs and humans, with a more rapid spread of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…The results showed that both HeV and NiV are well adapted to tRNAs pool of humans , but are poorly adapted to pig ’s tRNAs pool. This finding corroborated with an earlier study where NiV showed increased replication in humans as compared to pig primary airway epithelial cell cultures [ 58 ]. Furthermore, the gene-wise translation efficiency of henipaviruses was also calculated.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that both HeV and NiV are well adapted to tRNAs pool of humans , but are poorly adapted to pig ’s tRNAs pool. This finding corroborated with an earlier study where NiV showed increased replication in humans as compared to pig primary airway epithelial cell cultures [ 58 ]. Furthermore, the gene-wise translation efficiency of henipaviruses was also calculated.…”
Section: Discussionsupporting
confidence: 92%
“…A rapid spread of NiV is seen in human airway epithelia which express high levels of the NiV entry receptor ephrin-B2, and the expression levels vary between cells of different donors (Sauerhering et al. 2016). NiV infection upregulates IFN-λ in human respiratory epithelial cells.…”
Section: Nipah Virusmentioning
confidence: 99%
“…However, humans developed more severe disease with 40% case fatality rate compared to 1‐5% in pigs [ 40 ]. This difference in disease severity could be linked to higher expression of the receptor ephrin‐B2 on human tracheal and bronchial airway epithelial cells than in pigs, leading to more efficient infection [ 41 ]. NiV‐M did not transmit between humans and viral RNA was isolated from 30% of infected throat swabs [ 42 ]; therefore, it seems unlikely that infected humans posed a risk to pigs.…”
Section: Resultsmentioning
confidence: 99%